Palynological, Protein, and Phenolic Profiling of Bee Pollen from Mersin: An Investigation - ÇOBANOĞLU, Duygu Nur (ISPEC Tarım Bilimleri Dergisi, 2024)
Due to bee pollen’s exceptional nutritional profile and unique phenolic composition, it has received significant attention recently. The aim of this study was to investigate the botanical origin, protein content, and phenolic composition of the eight bee pollen samples (BP01–BP08) from different districts of Mersin city, Türkiye. According to palynological analysis, pollen grains of 51 taxa belonging to 25 families were determined. BP01 and BP07 were bifloral, and the other samples were multifloral. Pollen belonging to the genera Ceratonia sp., Helianthemum sp. and Olea sp. were predominant in the samples. The protein content values ranged from 23.1±1.23–28.1±1.49 g/100g. The presence of 23 phenolic compounds was investigated in bee pollen samples by liquid chromatography-tandem mass spectrometry (LC-MS/MS), and 12 of them were detected. Taxifolin, caffeic acid, quercetin, oleuropein, and kaempferol were determined to be the most abundant phenolic components, respectively. The bee pollen sample with the low protein content (BP03) had the highest phenolic composition. Furthermore, protein content and phenolic composition showed significant variability based on geographical origin.